2010
DOI: 10.1002/ange.201001259
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Overall Water Splitting Promoted by Two Different Cocatalysts for Hydrogen and Oxygen Evolution under Visible Light

Abstract: Harmonische Zusammenarbeit: Nanopartikel aus Mn3O4 und aus Kern/Schale‐strukturiertem Rh/Cr2O3 als Cokatalysatoren auf der Oberfläche eines GaN‐ZnO‐Mischkristalls als Katalysator beschleunigen die O2‐ bzw. H2‐Entwicklung unter sichtbarem Licht (λ>420 nm) und verbessern so die Wasserspaltungsaktivität gegenüber analogen Systemen, die nur mit Mn3O4 oder Rh/Cr2O3 modifiziert wurden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(111 citation statements)
references
References 25 publications
4
107
0
Order By: Relevance
“…Finally, the back-reaction can be prevented by creation of a protective oxide layer on the surface of the noble metal particles. This has been achieved for Rh promoted photocatalysts by deposition of a Cr 2 O 3 layer, as determined by Domen and coworkers [15]. This layer allows the hydrogen produced at the Rh surface to escape, but prevents the diffusion of oxygen to the metal surface necessary for the reaction of H 2 and O 2 [15].…”
Section: The Overall Water Splitting Reaction [5 and References Thermentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, the back-reaction can be prevented by creation of a protective oxide layer on the surface of the noble metal particles. This has been achieved for Rh promoted photocatalysts by deposition of a Cr 2 O 3 layer, as determined by Domen and coworkers [15]. This layer allows the hydrogen produced at the Rh surface to escape, but prevents the diffusion of oxygen to the metal surface necessary for the reaction of H 2 and O 2 [15].…”
Section: The Overall Water Splitting Reaction [5 and References Thermentioning
confidence: 98%
“…Solar panels for heating and production of electricity as such do not store energy, although batteries and chemical flow batteries are available and being improved. Two other major routes suggest themselves, for storing the collected photonic energy in the form of chemicals: -H 2 production by water splitting [11][12][13][14][15][16] -CO 2 reduction, combined with water oxidation (to O 2 ), yielding liquids such as alcohols or even hydrocarbons. This process is commonly referred to as artificial photosynthesis [17][18][19][20][21][22][23].…”
Section: Minerals (Including P and N In Suitable Formmentioning
confidence: 99%
“…We found that the photocatalytic activities of dual cocatalyst loaded Zn 2 GeO 4 samples are much higher than those loaded with only individual cocatalysts, and even higher than the sum of the two individual cocatalysts. 37 Figure 8 shows the photocatalytic activity for overall water splitting on Zn 2 GeO 4 coloaded with noble metals (Pt) and metal oxides (RuO 2 38 Recently, we also extended dual cocatalyst concept to Pt-RuO 2 /BiVO 4 photocatalyst for photocatalytic oxidation of thiophene using molecular O 2 as the electron acceptor, and 100% conversion efficiency of thiophene oxidation has been achieved. 39 Based on these experimental observations, we believe that dual cocatalyst approach is a general strategy for developing efficient photocatalytic systems.…”
Section: Dual Cocatalysts For Overall Water Splittingmentioning
confidence: 99%
“…For instance, sandwiched ZnO@Au@Cu2O nanorod films were synthesized on steel mesh substrates via a simple three-step approach and showed an efficient visible-light photocatalytic performance for the degradation of the MO solution [142]. Those non-doped ZnO hierarchical composites could also be used in the field of H2 generation [118,122,[143][144][145][146][147][148][149][150]. Barpuzary et al [143] prepared urchin-like CdS@ZnO hetero-arrays via a template-based method.…”
Section: Photocatalytic Applications Of Hierarchical Zno Nanostructurmentioning
confidence: 99%